2010
DOI: 10.1051/0004-6361/200811129
|View full text |Cite
|
Sign up to set email alerts
|

The dependence of X-ray AGN activity on host galaxy properties and environment

Abstract: There is mounting evidence that active galactic nuclei (AGN) selected through optical emission lines or radio luminosities comprise two distinct AGN populations, whose activity is triggered by different processes. In two previous papers, we studied the host galaxies and environment of radio-loud AGN. In this third paper we study the properties of a sample of Type-2 AGN that were selected on the basis of their [2-10] keV X-ray luminosity. We find that the X-ray luminosity function is in good agreement with prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…A mild mass dependence of the ERDFs is consistent with the data and would manifest itself in a mass dependent AGN fraction. Previous studies have reported AGN fractions that vary as a function of stellar mass (Best et al 2005;Kauffmann et al 2008;Hickox et al 2009;Silverman et al 2009;Xue et al 2010;Haggard et al 2010;Tasse et al 2011;Janssen et al 2012;Hernán-Caballero et al 2014;Williams & Röttgering 2015). However, when interpreting these results it is important to ensure that a possible selection effect has been accounted for.…”
Section: Agn Fractionmentioning
confidence: 99%
“…A mild mass dependence of the ERDFs is consistent with the data and would manifest itself in a mass dependent AGN fraction. Previous studies have reported AGN fractions that vary as a function of stellar mass (Best et al 2005;Kauffmann et al 2008;Hickox et al 2009;Silverman et al 2009;Xue et al 2010;Haggard et al 2010;Tasse et al 2011;Janssen et al 2012;Hernán-Caballero et al 2014;Williams & Röttgering 2015). However, when interpreting these results it is important to ensure that a possible selection effect has been accounted for.…”
Section: Agn Fractionmentioning
confidence: 99%
“…The relation between the chance for a galaxy to harbour an AGN and its stellar mass has been well-established for different manifestations of nuclear activity: optical (e.g., Kauffmann et al 2003a), radio (Best et al 2005), or X-ray (Tasse et al 2011). The larger the stellar mass, the higher the probability of harbouring an AGN.…”
Section: Properties Of the Host Galaxiesmentioning
confidence: 99%
“…Schawinski et al (2009Schawinski et al ( , 2010 found a clear relation are only available in electronic form at http://amiga.iaa.es/ and at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/545/A15 Appendix A is available in electronic form at http://www.aanda.org between some AGN and the signatures of a previous merger. In recent studies the relation between X-Ray AGN and environment was also explored (Silverman et al 2009;Haggard et al 2010;Tasse et al 2011), finding that this relation may depend on the mass of the host galaxy (Silverman et al 2009). Another possible source of discrepancy involves the methodology used to establish the presence of an AGN.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there have been a multitude of studies investigating the role of environment in relation to AGN activity, however, many of these give conflicting results due to the difficulty in comparing studies based on different depths, wavelengths, environment measures and redshift (e.g. Best 2004;Cooper et al 2005;Sorrentino et al 2006;Tasse et al 2011;Sabater et al 2013;Karouzos et al 2014a;Malavasi et al 2015).…”
Section: Introductionmentioning
confidence: 99%